Mode-Splitting for Refractive Index Sensing in Fluorescent Whispering Gallery Mode Microspheres with Broken Symmetry - Kang, Yvonne Q. (Sensors (Basel), 2018)
Whispering gallery mode (WGM) resonators have become increasingly diverse in terms of both architecture and applications, especially as refractometric sensors, allowing for unprecedented levels of sensitivity. However, like every refractometric sensor, a single WGM resonator cannot distinguish temperature variations from changes in the refractive index of the surrounding environment. Here, we investigate how breaking the symmetry of an otherwise perfect fluorescent microsphere, by covering half of the resonator with a high-refractive-index (RI) glue, might enable discrimination of changes in temperature from variations in the surrounding refractive index. This novel approach takes advantage of the difference of optical pathway experienced by WGMs circulating in different equatorial planes of a single microsphere resonator, which induces mode-splitting. We investigated the influence of the surrounding RI of the microsphere on mode-splitting through an evaluation of the sphere’s WGM spectrum and quality factor (Q-factor). Our results reveal that the magnitude of the mode-splitting increases as the refractive index contrast between the high-refractive-index (RI) glue and the surrounding environment increases, and that when they are equal no mode-splitting can be seen. Investigating the refractive index sensitivity of the individual sub modes resulting from the mode-splitting unveils a new methodology for RI sensing, and enables discrimination between surrounding refractive index changes and temperature changes, although it comes at the cost of an overall reduced refractive index sensitivity.